Tensile stress analysis against temperature variations with oil coolant in welding and heat treatment process - Syaiful Syaiful; Arminas; Mahlina Ekawati (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
Welding has become a very important technology in various manufacturing jobs in the industry. In the manufacturing industry, welding contributes significantly to increasing production efficiency. The purpose of this study was to determine the tensile stress value for each specimen variable resulting from the welding process, forming, heat treatment and tensile testing on the specimen. The study used an experimental method with the number of specimens to be tested as many as 15 specimens from 5 temperature variations used. Low carbon steel plates are first welded using welding techniques, electrode types, welding positions, and weld locations, and specimen formation is carried out according to the ASTM E8 plate tensile test standard. Then heat treatment is carried out with variations in temperature and oil cooling media, the results of the heat treatment process will then be tensile tested on each specimen. The results showed that the tensile stress results obtained for the welding process specimens at a temperature of 700 °C and oil cooling media had the highest stress value of 13.25 N/mm2. There was a decrease in tensile stress at other temperature variations, while for specimens with a temperature of 500 °C and oil cooling media had the lowest stress value of 11.79 N/mm2. Testing using high temperatures can increase the tensile stress value, due to the increase in material strength in the specimen during the heat treatment process.